Does Globalization Worsen Environmental Quality in ASEAN Countries? - Stannia Cahaya Suci; Vadilla Mutia Zahara; Rah Adi Fahmi Ginanjar; Cep Jandi Anwar (Department of Development Economics, Universitas Sriwijaya, 2022)
The era of globalization, which is characterized by integration between economies, increases world output, but environmental damage becomes an important concern to achieve sustainable growth. Therefore, this study intends to estimate the impact of globalization in economic, social side and political terms together with the variables of GDP per capita, financial development and energy spending on carbon emissions and to prove the presence of Kuznets Environmental Curve Hypothesis in ASEAN using panel data over 2000-2019 period. The results of the study proved that globalization, especially social globalization, and energy consumption have role in escalating environmental damage. GDP per capita is found in the reduction of carbon emissions but financial development was discovered to have no significant impact on increasing carbon emissions. This study does not prove the presence of EKC. Hence, this proposes crucial implications for policy makers. These findings suggest that the policy makers to make sustainable energy development strategies while increasing regional income and economic development through globalization.